Implementasi Metode Tahfizh dalam Pembelajaran Al-Qur’an di MI Al-Wathoniyyah Bekasi Timur - Hafizah Dian Apricellina; Siti Asiah (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2016)
This study aimed to describe the method tahfizh in learning the Qur'an in Islamic Basic School (MI) Al-Wathoniyyah East Bekasi. This study used qualitative methods naturalistic, the research intends to understand the phenomena experienced by research subjects, such behavior, perception, motivation, action as a whole, by describing it in the form of words and language, in a specific context in which the natural by utilizing various methods natural. The results of this study indicate that the implementation of the method tahfizh in learning the Qur'an in Islamic Basic School (MI) Al-Wathoniyyah East Bekasi already well underway, although not all students are able to read the Qur'an but helped with the infrastructure and facilities adequate education as well as teachers competent in learning tahfizhul Qur'an. And methods tahfizh implemented are in accordance with the theory (tahfizh) are presented in chapters II and learning outcomes tahfiz al-Qur’an obtained in accordance with the Qur'an recitation of the Qur'an targets specified.